The utility of pentraxin 3 and platelet-derived growth factor receptor beta as non-invasive biomarkers for prediction of cardiovascular risk in MAFLD patients - Hanaa Badran; Maha Elsabaawy; Mahmoud Magdy; Samar Ghanem; Mohammed Said; Mohamed Hamdy Torky; Tamer Samir (SpringerOpen, 2024)
Abstract Background Metabolic-associated fatty liver disease (MAFLD) has emerged as the predominant form of chronic liver disease globally linked with heightened cardiovascular disease (CVD) risk, the leading cause of mortality among affected individuals. Aim This study aims to assess serum PTX3 (pentraxin 3) and platelet-derived growth factor receptor beta (PDGFRβ) as potential non-invasive biomarkers for predicting cardiovascular risk (CVR) in MAFLD patients. Method A case-control investigation encompassing 84 MAFLD patients without prior CVD history and 30 age- and gender-matched healthy controls was conducted. Both cohorts underwent comprehensive laboratory and radiological evaluations. CVR was evaluated through common carotid artery intima-media thickness (IMT), Framingham risk score, and QRISK 2 score. The efficacy of two ELISA biomarkers PTX3 and PDGFRβ was examined for correlation with CVR in MAFLD patients. Results MAFLD patients displayed significantly heightened levels of PTX3 and PDGFβ compared to healthy controls (P < 0.001, P = 0.016, respectively). PDGFβ exhibited a notably positive correlation with the Framingham score (P = 0.016), while no significant correlation was observed with pentraxin 3 (P = 0.061). Univariate and multivariate analyses identified diabetes mellitus (DM) (P < 0.001*), hypertension (P = 0.005), visceral fat (P < 0.001*), waist/hip circumference (P = 0.04), and PDGFβ (P = 0.03) as robust predictors of CVR, with PTX3 demonstrating limited prognostic utility. Conclusion PDGFβ emerged as a promising early non-invasive predictor of CVR in MAFLD patients, highlighting its potential role in guiding tailored preventive interventions, while PTX3 exhibited a modest impact warranting further investigation.